2006
DOI: 10.1098/rspb.2006.3716
|View full text |Cite
|
Sign up to set email alerts
|

The re-emergence of felid camouflage with the decay of predator recognition in deer under relaxed selection

Abstract: When a previously common predator disappears owing to local extinction, the strong source of natural selection on prey to visually recognize that predator becomes relaxed. At present, we do not know the extent to which recognition of a specific predator is generalized to similar looking predators or how a specific predator-recognition cue, such as coat pattern, degrades under prolonged relaxed selection. Using predator models, we show that deer exhibit a more rapid and stronger antipredator response to their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…Although many studies have investigated the existence of predator recognition in a variety of species, very little is known about the specific characteristics of the predator that the prey learn to recognize. Three recent studies have revolutionized the way in which ecologists view predator recognition (Griffin et al 2001;Ferrari et al 2007;Stankowich & Coss 2007). These studies revealed that prey animals have the ability to display an antipredator response to a novel predator if it is closely related to a predator they recently learned to recognize.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have investigated the existence of predator recognition in a variety of species, very little is known about the specific characteristics of the predator that the prey learn to recognize. Three recent studies have revolutionized the way in which ecologists view predator recognition (Griffin et al 2001;Ferrari et al 2007;Stankowich & Coss 2007). These studies revealed that prey animals have the ability to display an antipredator response to a novel predator if it is closely related to a predator they recently learned to recognize.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, deer did not respond to model jaguars. Stankowich & Coss (2007) attributed their results to the spotted pattern of the jaguar's coat, which would camouflage the jaguar's body shape. These results indicate that learned predator recognition requires labelling of specific characteristics of predators and that predatory traits shared by closely related species of predators can be used by prey to label them as dangerous, prior to any experience with the novel threats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress needs to be made on rectifying this issue as several strands of evidence suggest that form is as least as important as color in determining signal information content. For example, shape information is involved in predator learning of noxiousness [Hauglund, 2006;Niskanen and Mappes, 2005], inter and intraspecific recognition [Fordyce et al, 2002;Stankowich and Coss, 2007] and mate choice [Alatalo et al, 1988]. Symmetry is a property of shape and pattern that can also have an important signaling function in primates .…”
Section: Analyzing Shape and Patternmentioning
confidence: 99%
“…These models were used in previous research on the antipredator behavior of Columbian black-tailed deer (O. h. columbianus; see Figure 1 in Stankowich & Coss, 2007). The leopard and deer models constructed of lifesized photographs were scaled to have approximately the same total surface area and similar body lengths (1.5 m).…”
Section: Animal Modelsmentioning
confidence: 99%